Zonas homogéneas para manejo específico por sitio en maíz usando un sensor de inducción electromagnética en la sabana de Bogotá (2015)
Precision farming aims to improve production taking into account variability of the agricultural system. To do this, homogeneous management zones (HZ) are delimited within the crop field. The use of electromagnetic induction (EMI) sensors that record apparent electrical conductivity (ECa) allows to identify variations in soil properties and in turn to define quickly and reliably zones with similar characteristics. The research had as objective ZM delimitation for site-specific management (SSM) using an EMI sensor in soils under maize crops (Zea mays L.) at the Sabana de Bogotá. For this, two agricultural fields were chosen in Facatativá and Bojacá, and in them it was measured ECa and soil water content (Wsc). Maps of ECa and Wsc were drawn and three ZM were defined within each field. In these ZM, soil samples were taken for physicochemical laboratory analysis and it was determined plant height, SPAD index at 60 and 120 DDG and crop yield. Statistical analysis was performed with SPSS V22 and SAS V 2.5. The results showed correlations between ECa and content of silt in Bojacá and clay content in Facatativá, and statistically significant differences in maize yields between the ZM. This research highlights the utility of the IM sensor to define ZM for SSM.